Education enrollment rate vs employment rate: Implications for sustainable human capital development in Nigeria - Opeyemi Oluwabunmi Adejumo; Simplice Asongu; Akintoye Victor Adejumo (African Governance and Development Institute (AGDI), 2021)
The study examines the dynamic interrelationships among the school enrolment rates and the rate of employment (via unemployment rates) in Nigeria. The study employed Autoregressive estimates and an unrestricted VAR approach to analyze these relationships. The study lends credence to the new-growth theory (i.e. endogenous models) that more investments in human capital, through education especially at higher levels, will allow human capital to evolve dynamically and increase long-run growth in Nigeria. This tendency engenders multiplier effects in stimulating sustainable development given that education-driven growth facilitates employment. The growth literature has been definitive on the role of human capital in achieving long-run economic growth. Therefore, investments in education have been identified as a vital channel for building human capital and achieving long run development objectives. Thus, in the nascent quest for sustainable development, this study takes the new growth theory a step higher by examining the modulating effects of educational-driven growth (i.e. via school enrolments rates) in setting the pace for employment patterns in Nigeria.
Keywords: I21; I31; O40; O55; 330; Education; Employment; Human Capital; Enrolment; Development